2014
DOI: 10.1080/09603107.2014.924297
|View full text |Cite
|
Sign up to set email alerts
|

Predicting BRICS stock returns using ARFIMA models

Abstract: This paper examines the existence of long memory in daily stock market returns from Brazil, Russia, India, China, and South Africa (BRICS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…The findings revealed that there exists positive correlation between all the four series. Aye et al (2012) examined the existence of long memory in daily stock market returns from BRICS countries using Autoregressive Fractionally Integrated Moving Average (ARFIMA) models in predicting stock returns. The outcome suggested that ARFIMA models produced better forecasting results than the non-ARFIMA (AR, MA, ARMA and GARCH) models.…”
Section: Us-brics Marketsmentioning
confidence: 99%
“…The findings revealed that there exists positive correlation between all the four series. Aye et al (2012) examined the existence of long memory in daily stock market returns from BRICS countries using Autoregressive Fractionally Integrated Moving Average (ARFIMA) models in predicting stock returns. The outcome suggested that ARFIMA models produced better forecasting results than the non-ARFIMA (AR, MA, ARMA and GARCH) models.…”
Section: Us-brics Marketsmentioning
confidence: 99%
“…As far as the econometric framework is concerned, unlike the existing studies on modeling volatility of the BRICS stock markets based on univariate models from the generalized autoregressive conditional heteroskedasticity (GARCH)-family (see for example, Babikir et al, (2012), Aye et al, (2014), Kishor & Singh (2014), Adu et al, (2015), Bouri et al, (2018) for detailed reviews), we use the GARCH variant of the mixed data sampling (MIDAS), i.e., the GARCH-MIDAS model. The reason behind this is that, while stock market data is at a daily frequency, the oil shocks used as predictors are available only at the monthly frequency, and hence the modeling of volatility requires a MIDAS-based approach.…”
Section: Introductionmentioning
confidence: 99%
“…From several previous studies, the ARFIMA model build predictive values with better accuracy than other models because it has flexibility, robustness and able to accommodate long memory effects, including (Kartikasari, 2020) show that the ARFIMA model show better result than the LSTAR and FILSTAR models. Aye et al, (2014) examines the effect of long memory daily stock returns from Brazil, Russia, India, China, and South Africa, also explain the efficacy of the ARFIMA model. (Baillie & Morana, 2012) examines simple adaptive modification of the basic ARFIMA model using the flexible Fourier form which is enable for a variety of interceptions In the long memory case the stationary process causes the autocorrelation function to slow down slowly.…”
Section: Arfima Modelmentioning
confidence: 99%